2007
DOI: 10.1017/s0950268807008333
|View full text |Cite
|
Sign up to set email alerts
|

Investigating urban–rural disparities in tuberculosis treatment outcome in England and Wales

Abstract: SUMMARYThe purpose of this study was to compare the occurrence of tuberculosis (TB) and the outcome of treatment between TB patients living in urban and rural areas. Cases of TB reported from 2001 to 2003 in England and Wales were assigned to a rural or urban area classification. The outcome of interest, non-completion of treatment, was investigated to determine the odds ratio for urban vs. rural residence. The effects of age, sex, ethnicity, place of birth, time since arrival in the United Kingdom, disease si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
(10 reference statements)
3
18
2
Order By: Relevance
“…China, where on average 67% of the population belonged to an agricultural population. A recent nationwide survey showed that the prevalence of TB was relatively higher in rural areas than in urban areas, which is not the case in low-incidence countries [19]. The surprisingly low clustering found in this study, in contrast to places such as South Africa, which has co-infection of TB and human immunodeficiency virus (HIV) and explosive outbreaks (i.e.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…China, where on average 67% of the population belonged to an agricultural population. A recent nationwide survey showed that the prevalence of TB was relatively higher in rural areas than in urban areas, which is not the case in low-incidence countries [19]. The surprisingly low clustering found in this study, in contrast to places such as South Africa, which has co-infection of TB and human immunodeficiency virus (HIV) and explosive outbreaks (i.e.…”
Section: Discussioncontrasting
confidence: 82%
“…We used a combination of molecular methods and epidemiological data to determine the genetic diversity of circulating Mtb strains, and provide the estimates of recent transmission and risk factors for clustering among pulmonary TB patients in rural China, where on average 67% of the population belonged to an agricultural population. A recent nationwide survey showed that the prevalence of TB was relatively higher in rural areas than in urban areas, which is not the case in low‐incidence countries . The surprisingly low clustering found in this study, in contrast to places such as South Africa, which has co‐infection of TB and human immunodeficiency virus (HIV) and explosive outbreaks (i.e.…”
Section: Discussioncontrasting
confidence: 80%
“…Health care service delivery is better in urban populations because health facilities are easy to reach whereas rural patients must travel long distances. [10,11] Additionally, urban settings have more skilled health care providers with more clinical experience in the management of TB and HIV and access to better diagnostics. In contrast, most TB patients in urban settings are from deprived communities and social disadvantages such as slums which may contribute to poorer TB treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, most TB patients in urban settings are from deprived communities and social disadvantages such as slums which may contribute to poorer TB treatment outcomes. [10] We examined the prevalence of recurrent TB among TB cases notified to the National TB Program (NTP) in southern province of Zambia. We assessed for risk factors associated with death, loss to follow up and failure among recurrent TB patients accessing treatment at health facilities in rural and urban settings.…”
Section: Introductionmentioning
confidence: 99%
“…If every person with, for example, a cough lasting 3 weeks is investigated for tuberculosis, this will result in significant unnecessary investigation, especially in primary care. With <9000 cases in a population of 60 million, the majority of whom are resident in urban areas,3 the average general practitioner in a rural area in the UK may not see a single case of tuberculosis in several years.…”
mentioning
confidence: 99%